2010
DOI: 10.48550/arxiv.1001.2242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Twisted cohomology for hyperbolic three manifolds

Abstract: For a complete hyperbolic three manifold M , we consider the representations of π 1 (M ) obtained by composing a lift of the holonomy with complex finite dimensional representations of SL(2, C). We prove a vanishing result for the cohomology of M with coefficients twisted by these representations, using techniques of Matsushima-Murakami. We give some applications to local rigidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…More interestingly, the converse holds: the torsions τ(X m , α m ) determine T K (see Theorem 4.5). This latter result follows from work of David Fried [Fri] (see also Hillar [Hil]) and that of Menal-Ferrer and Porti [MFP1].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…More interestingly, the converse holds: the torsions τ(X m , α m ) determine T K (see Theorem 4.5). This latter result follows from work of David Fried [Fri] (see also Hillar [Hil]) and that of Menal-Ferrer and Porti [MFP1].…”
Section: Introductionsupporting
confidence: 54%
“…The torsions τ(X m , α m ) are interesting invariants in their own right. For example, Menal-Ferrer and Porti [MFP1] showed that τ(X m , α m ) is non-zero for any m. Furthermore, Porti [Por1] showed that τ(X 1 , α 1 ) = τ(X , α) = T K (1) is not obviously related to hyperbolic volume. More precisely, using a variation on [Por2,Théorème 4.17] one can show that there exists a sequence of knots K n whose volumes converge to a positive real number, but the numbers T K n (1) converge to zero.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, every representation ρ := ρ(m) of G also defines a flat vector bundle E ρ over X. Now by our assumption (2.2) on Γ and [MePo1,Proposition 2.8], the cohomology H * (X, ρ) never vanishes. Thus in order to define the Reidemeister torsion of E ρ , one needs to fix bases in the homology H * (X, ρ).…”
Section: Introductionmentioning
confidence: 94%
“…However, this is no longer the case for the representations σ k , k ∈ Z − 1 2 Z. Furthermore, Theorem 1.2 can not be applied to a group Γ ′ corresponding to an acyclic spin-structure of X since by [MePo1,Lemma 2.4] such a group never satisfies the assumption (2.2). This assmuption is yet needed for our compuations involving the Selberg trace formula and in order to apply the results about the meromorphic continuation of the zeta functions obtained in [Pf].…”
Section: Introductionmentioning
confidence: 99%
“…Fix for each j a nonzero vector ω j (m) ∈ V (m) fixed under ρ(m)(π 1 (T j )). The set of such vectors is a onedimensional complex vector space, see [MePo1,Lemma 2.4]. Fix moreover for each j a non-trivial cylce θ j ∈ H 1 (T j ; Z) and let η j ∈ H 2 (T j ; Z) be a Z-generator of H 2 (T j ; Z).…”
Section: Ruelle Zeta Functions and The Asymptotics Of Normalized Reid...mentioning
confidence: 99%